Revisiting the link between domain satisfaction and life satisfaction during the COVID-19 pandemic: Job-related moderators in triadic analysis in dual-earner parents with adolescent children - Schnettler, Berta; Concha-Salgado, Andrés; Orellana, Ligia; Saracostti, Mahia; Miranda-Zapata, Edgardo; Poblete, Héctor; Lobos, Germán; Adasme-Berríos, Cristian; Lapo, María; Beroíza, Katherine; Riquelme, Leonor (Frontiers in Public Health, 2023)
Research has evaluated the impact of COVID-19 pandemic and lockdowns on individuals’ life satisfaction, but well-being interrelations between family members in this context have been less explored. This study examined the spillover and crossover effects of one parent’s job satisfaction (JS), satisfaction with family life (SWFaL) and satisfaction with food-related life (SWFoL) on their own, their partner’s, and their adolescent children’s life satisfaction (LS), and the influence of adolescents’ SWFaL and SWFoL on their own and their parents’ LS, in dual-earner families with adolescents. The moderating role of job-related variables of both parents were also explored. Questionnaires were administered to 860 dual-earner parents with adolescents in two cities in Chile during 2020. Mothers and fathers answered the Overall Job Satisfaction Scale and the three family members answered the Satisfaction with Life Scale, the Satisfaction with Family Life Scale and the Satisfaction with Food-related Life Scale. Using the Actor-Partner Interdependence Model and structural equation modeling, we found that fathers’ LS was positively associated with their own JS, SWFaL and SWFoL (spillover), and negatively with adolescents’ SWFoL (crossover). Likewise, mothers’ LS was positively associated with their own JS, SWFaL and SWFoL (spillover), with fathers’ and adolescents’ SWFaL, and negatively with adolescents’ SWFoL. Adolescents’ LS was positively associated with their own SWFaL and SWFoL (spillover), and with their fathers’ JS, and negatively with their fathers’ SWFoL. JS showed gendered patterns in spillover and crossover associations. Parents’ type of employment, mothers’ working hours and city of residence moderated some spillover and crossover associations for father-mother and parent-adolescent dyads. These findings suggest that, for dual-earner parents with adolescents, improving individuals’ LS requires interventions that should be carried out not individually, but at a family level.